Phosphorus decreases in Lake Geneva but climate warming hampers the recovery of pristine oligochaete communities whereas chironomids are less affected - Claude Lang (Journal of Limnology, 2016)
In response to the decrease of phosphorus concentrations in Lake Geneva (France and Switzerland), the mean percentage of individuals belonging to oligochaete species sensitive to low oxygen concentrations has increased in the profundal from 8% in 1983 to 31% in 2003. But these species decreased anew from 17% in 1999 to 2% in 2009 in the western basin of Lake Geneva (the Small Lake). This shallow basin is more exposed to the effects of warming observed since 1989 than the rest of the lake. To demonstrate these effects, the response of the main species to the increase of organic sedimentation was analysed in the gradient of fine sediment accumulation (FSA), observed in 1999 in the Small Lake. As expected, the abundance of four species classified as sensitive to low oxygen concentrations - Stylodrilus lemani, Embolocephalus velutinus, Bichaeta sanguinea, Paracladopelma nigritula gr. - decreased with the increase of FSA whereas the inverse relationship was observed for four species classified as tolerant Potamothrix vejdovskyi or very tolerant P. hammoniensis, P. heuscheri, and Tubifex tubifex. In contrast, the abundance of three species was not correlated with FSA: Stylodrilus heringianus and Micropsectra contracta both classified as sensitive, Limnodrilus hoffmeisteri as tolerant. The first component of a principal component analysis, based on the mean abundance per transect of the above species, was correlated with FSA. The second component could reflect the long-term increase of water temperature which has been advantageous for Limnodrilus and Micropsectra but disadvantageous for the sensitive oligochaete species less adapted to warm water lakes. Indeed, the abundance of the sensitive oligochaete species and of P. vejdovskyi has decreased from 1994 to 2009 in the Small Lake whereas the abundance of Limnodrilus has increased. Micropsectra and Paracladopelma became more abundant than sensitive oligochaete species. In addition to the effects of temperature, the recovery of the pristine oligochaete community was perhaps impeded in 2009 because the transfer of organic matter to the sediment was increased by the impact of fish (mostly Coregonus) feeding selectively on zooplankton. Finally, many micro pollutants (pesticides, drugs, and other substances) which are present in the lake could have negatively affected sensitive oligochaete species.